Perlindungan Hukum kepada Musisi Lokal dari Tindakan Bootleg T-Shirt Ditinjau Melalui Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis Juncto Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Andinie Zanatine; Neni Sri Imaniyati; Muhammad Ilman Abidin (UNISBA Press, 2024)
Abstract. Musicians create works such as songs, often released in physical formats like vinyl records and cassette tapes, and increasingly use merchandise as a key connection with their fans. However, the rise of